Underwater Digital Twin of Yuba Island: Mapping a Large-Scale Marine Ecosystem through Photogrammetry and 3D Modeling - C. Gerigk (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The project involved creating a high-resolution digital twin of the underwater environment surrounding Yuba Island, a pristine site in the Red Sea, Saudi Arabia. The goal was to replicate the experience of diving in this environment, 3D mapping approximately 147 ha underwater and 290 ha above water, completed within six months. The 3D model was designed to be highly accurate, featuring true-to-life textures and colors, and georeferenced with a depth accuracy of ±0.10 m relative to local Mean Sea Level (MSL). The mapping covered coral reefs, fringing reefs, pinnacles, sand, caves, channels, and overhead environments, covering depths from 0.5 m to 70 m, mapped at 4.5 m2/s and 1 mm/px resolution. Over 100 local fish species were documented, 3D-modeled, and incorporated with behavioral metadata to simulate natural marine life. Final deliverables included Cesium tilesets, a Virtual Reality (VR) Cube experience, and a desktop version of the model. The project team included specialists in underwater photogrammetry, commercial diving, marine biology, oceanography, software development, data engineering, and VR design, all working together to deliver the Underwater Digital Twin within the six-month timeline.